2004
DOI: 10.1111/j.1537-2995.2004.04010.x
|View full text |Cite
|
Sign up to set email alerts
|

Storage of platelets in additive solution for up to 12 days with maintenance of good in‐vitro quality

Abstract: In-vitro quality of PCs in AS with at least 35-percent plasma can be maintained for 7 to 12 days after collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 29 publications
8
66
0
Order By: Relevance
“…The platelet content of the products was measured directly after production, because a previous study has shown a limited decline in platelet number during 5 days of storage. 4,23 We found significant differences with regard to pH and platelet content of the 2 PCs. The lower pH of PAS II PCs is due to a lower intrinsic pH of PAS II, lower buffering capacity, and higher lactate production.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The platelet content of the products was measured directly after production, because a previous study has shown a limited decline in platelet number during 5 days of storage. 4,23 We found significant differences with regard to pH and platelet content of the 2 PCs. The lower pH of PAS II PCs is due to a lower intrinsic pH of PAS II, lower buffering capacity, and higher lactate production.…”
Section: Discussionmentioning
confidence: 71%
“…Although in vitro studies showed significant differences suggesting inferior quality in metabolic, functional, and flow cytometric parameters in platelets stored in PAS II as compared with plasma, platelets stored up to 5 days in PAS II stay within the range of minimal quality requirements. [3][4][5][6] The correlation of these in vitro parameters with clinical efficacy is inconsistent. [7][8][9] One paired radiolabeled platelet survival study showed a significant decrease in both recovery as well as survival of PAS II PCs compared with plasma PCs and PCs stored in PlasmaLyte A (Baxter, Deerfield, IL).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to previous observations in conventional PCs after 12 days storage, increasing pH was observed from Day 7 in PCT PCs, corresponding to marked reduction in PLT concentration and glucose depletion. 53 High PLT concentrations have previously been shown correlated with low pH at single observation points, 54,55 suggesting that decreasing PLT concentrations might stabilize pH levels. A decrease in pH during storage of PLTs in a synthetic medium, however, will also stop when all glucose is consumed.…”
Section: Discussionmentioning
confidence: 96%
“…These electrolytes inhibit platelet activation and aggregation, although how they work is unclear. 34 Van der Meer and colleagues 35 compared the in vitro storage characteristics of pooled buffy coat platelets stored for up to 12 days in 100% plasma, or in mixtures of plasma with PAS-II, PAS-III, PAS-IIIM and Composol. They observed that several in vitro markers of platelet quality (pH ≥ 6.8, glucose consumption, lactate production) were reasonably well preserved for 9-12 days in platelets stored either in 100% plasma, or in PAS-IIIM (30% plasma) or Composol (35% plasma).…”
Section: Additive Solutionsmentioning
confidence: 99%